Surgicopathological Quality Control and Protocol Adherence to Lymphadenectomy in the CRITICS Gastric Cancer Trial. Issue 6 (December 2018) - Claassen, Yvette H. M.; de Steur, Wobbe O.; Hartgrink, Henk H.; Dikken, Johan L.; van Sandick, Johanna W.; van Grieken, Nicole C. T.; Cats, Annemiek; Trip, Anouk K.; Jansen, Edwin P. M.; Kranenbarg, Willemina M. Meershoek-Klein; Braak, Jeffrey P. B. M.; Putter, Hein; et al.
Abstract : Objective: The purpose of this study was to evaluate surgicopathological quality and protocol adherence for lymphadenectomy in the CRITICS trial. Summary of Background Data: Surgical quality assurance is a key element in multimodal studies for gastric cancer. In the multicenter CRITICS trial (ChemoRadiotherapy after Induction chemotherapy In Cancer of the Stomach), patients with resectable gastric cancer were randomized for preoperative chemotherapy, followed by gastrectomy with a D1+ lymphadenectomy (removal of stations 1 to 9 and 11), followed by either chemotherapy or chemoradiotherapy. Methods: Surgicopathological compliance was defined as removal of ≥15 lymph nodes. Surgical compliance was defined as removal of the indicated lymph node stations. Surgical contamination was defined as removal of lymph node stations that should be left in situ. The Maruyama Index (MI, lower is better), which has proven to be an indicator of surgical quality and is strongly associated with survival, was analyzed. Results: Between 2007 and 2015, 788 patients were randomized, of whom 636 patients underwent a gastrectomy with curative intent. Surgicopathological compliance occurred in 72.8% (n = 460) of the patients and improved from 55.0% (2007) to 90.0% (2015). Surgical compliance occurred in 41.1% (n = 256). Surgical contamination occurred in 59.6% (n = 371). Median MI was 1 (range 0 to 136). Conclusion: Surgical quality in the CRITICS trial was excellent, with a MI of 1. Surgicopathological compliance improved over the years. This might be explained by the quality assurance program within the study and centralization of gastric cancer surgery in the Netherlands.